Adjunctive treatment with low dose intra-arterial eptifibatide and intravenous aspirin during carotid stenting: A case series. (February 2021) - Horev, Anat; Zlotnik, Yair; Borodetsky, Vladimir; Biederko, Ron; Star, Michael; Zvenigorodsky, Vladislav; Shelef, Ilan; Ifergane, Gal
Highlights: Changing medication regimen during Carotid stenting may decrease acute thrombotic events. Changing medication regimen during Carotid stenting may decrease delayed thrombotic events. Carotid stenting is a safe procedure with a low percentage of complications. Using Low Dose Intra-arterial Eptifibatide in a low dose may decrease the complication rate during Carotid stenting. Abstract: Purpose: According to most guidelines, medical protocol for carotid stenting includes the administration of oral Aspirin and Clopidogrel at least four days before the procedure, with intraprocedural intravenous (IV) heparin. Some publications have also reported the safety of adding glycoprotein 2b/3a inhibitors to the protocol. In this retrospective study, we evaluate the safety of a new medication protocol that includes IV aspirin and intra-arterial Eptifibatide (glycoprotein 2b/3a inhibitor) during carotid stenting. All patients who underwent carotid stenting at Soroka University Medical Center between January 2015 and May 2020 were included (emergent cases were excluded). We divided patients into two groups—patients treated under the standard protocol, and patients treated under the new protocol. In the latter, patients received both the standard protocol regimen, as well as 150 mg IV aspirin immediately before stenting, and a slow intra-arterial injection of 2–3 mg Eptifibatide (glycoprotein 2b/3a antagonist) immediately after stenting. Forty-four patients were treated according to the standard protocol (group 1), and 41 patients were treated according to the new protocol (group 2). In group 1, six patients had complications, while in group 2, no complications of any kind were noted (p = 0.027). The safety and possible efficacy of this novel protocol was preliminarily demonstrated in the present study. Future studies are needed to prove the safety and efficacy of a specific drug regimen that will further reduce the complication rates of carotid stenting.